Hubungan Antara Dukungan Sosial Dengan Kesepian Pada Mahasiswa Tingkat Awal - Benediktus Dadya Setyowidi; Emmanuel Satyo Yuwono (Journal of Innovation Research and Knowledge, 2026)
The transition from high school to higher education is a challenging period for first-year college students. Various adaptation demands toward a more independent educational system and a new environment frequently trigger psychological distress, such as loneliness. This study aims to determine the relationship between social support and loneliness among first-year students (class of 2025) at Universitas Kristen Satya Wacana (UKSW) Salatiga. The research method employed a correlational quantitative approach. Data collection utilized two main instruments: the Social Support Scale and the UCLA Loneliness Scale Version 3, distributed to a sample of students from the class of 2025. Data analysis was conducted using Spearman's Rank correlation technique due to the non-normal distribution of the data. The statistical analysis results indicated a correlation coefficient rs of -0.184 with a significance level p of 0.000 (p less than 0.05). These findings demonstrate that there is a significant negative relationship between social support and loneliness among first-year students. The higher the perceived social support received, the lower the level of loneliness experienced by the students, and vice versa. The conclusion of this study confirms that social support plays a critical role as a protective factor in reducing student loneliness during the academic transition. Educational institutions are advised to optimize psychosocial development programs and encourage a supportive peer environment for freshmen.